2011
DOI: 10.1038/npre.2011.6693
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid features: a missing compartment of prediction of protein function

Abstract: Enormous computational efforts have been carried out to predict structure and function of protein. However, nearly all of these efforts have been focused on prediction of function based on primary nucleic acid sequence or modelling 3D structure of protein from its nucleic acid sequence. In fact, it seems that amino acid attributes, which is an intermediate phase between DNA/RNA and advanced protein structure, have been missed. 2 EMC can vary from 0.0% to 100%, depending upon which attribute weighting algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Our results of higher propensities of polar amino acids of Gln and Ser are consistent with the studies reported in literature. [79] Several other studies [80][81][82] have also shown that amino acid compositions, especially polar amino acids (Gln, Ser) play an important role in enhancing molecular hydrophilicity and impart recognizable effects on thermostability of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Our results of higher propensities of polar amino acids of Gln and Ser are consistent with the studies reported in literature. [79] Several other studies [80][81][82] have also shown that amino acid compositions, especially polar amino acids (Gln, Ser) play an important role in enhancing molecular hydrophilicity and impart recognizable effects on thermostability of proteins.…”
Section: Discussionmentioning
confidence: 99%